APACHE II Scoring System and its Probability Impact in Poly Trauma Patients at a Tertiary Care Center - Ahmad Maeem Akhtar, Nazia Farooq, Maheen Qasim, M. Rehman Gulzar, Khalil ur Rehman, Muhhamd Ammar Noor, Mehar un Nisa (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Trauma is one of the most significant causes for in hospital mortality. Different predictors are available to predict the patient outcome like revised trauma scoring system (physiological), Injury severity scoring system (Anatomical scoring system), APACHE II, AIS etc. Aim: To assess pobability of APACHE II score in evaluating mortality for poly trauma patients within first 24 hr of hospitalization. Method: Cross sectional study was conducted at surgical unit in Lahore General Hospital, Lahore from Jan, 2019 to Dec, 2020. APACHE II for each patient was calculated with devised software APACHE II Score- MDCalc. After fulfilling the inclusion and exclusion criteria, 300 patients were included in the study from emergency department of a tertiary care hospital. All the data was entered in proforma and was analyzed in SPSS 23. Results: Mean age was 32.53 ± 11.67 years with 205 (68.33%) male and 95(31.67%) were female patients. Out of 300, in hospital mortality occurred in 88(29.33%) while other 212(70.66%) were alive within 24 hours after admission. 88(29.33%) patients out of 300 had probability APACHE II score ≥ 12 and rest 212(70.66%) had ≤ 12. The sensitivity, specificity, PPV, NPV, and diagnostic accuracy of APACHE II was 90.16%, 94.2%, 88%, 92.84% and 90.74%. Conclusion: By using APACHE II scoring system for poly trauma patients we can devise an efficient treatment and resuscitation plan to reduce the probability of hospital mortality. Keywords: Trauma, prediction, mortality, APACHE II.